Do Financial Access, Digitalization Adoption, Innovation, and Market Orientation Influence Business Performance of Micro-Small Enterprises? - Ida Puspitowati; Carunia Mulya Firdausy; Sarwo Edy Handoyo (Universitas 17 Agustus 1945 Semarang, 2024)
The improvement of performance for Micro and Small Enterprises (MSEs) is a must to achieve business performance growth. To achieve business performance successfully, the MSEs partly need to investigate factors that influence it. This study aims to examine whether or not financial access, digitalization adoption, product innovation, and market orientation influence MSEs' business performance. The source of data was obtained by distributing questionnaires to 135 women who engaged in MSEs in Belitung Regency as one of the main locations of women MSEs in Indonesia. These data were then analyzed statistically by applying the Partial Least Square-Structural Equation Modeling (PLS-SEM. The main findings of this research are: (i) the path coefficient of the variables financial access, product innovation, and market orientation has a positive and significant effect, (ii) the path coefficient of digitalization adoption has a positive but not significant effect on MSE business performance. The results of this research provide input for women's MSEs in Belitung Regency to be able to improve their market orientation to overcome marketing obstacles that may be experienced and to improve the business performance of women's MSEs in Belitung Regency.